المجاهد عمار بن عودة - سناء بن التواتي; د/ مارية الشارف (جامعة عمار ثليجي الاغواط, 2025)
ملخص باللغة العربية: تندرج هذه الدراسةضمن البحوث التاريخية التي تُعنى بتوثيق نضال شعبنا وتسليط الضوء على الرموز الفاعلة في ثورتنا المجيدة، وخاصة ثورة نوفمبر الخالدة. وقد سعينا من خلال هذا الموضوع إلى إبراز شخصية المجاهد والقائد عمار بن عودة – رحمه الله – الذي يُعد أحد الأسماء اللامعة في تاريخنا الوطني. ركّزت في هذا العمل على استكشاف أبعاد شخصيته، ودوره المحوري في المراحل التي سبقت اندلاع الثورة الجزائرية، خصوصًا من خلال نشاطه في المنظمة السرية العسكرية، وكذلك إسهامه في اتخاذ قرار تفجير الثورة والإعداد لها. ولم يقتصر دوره على تلك الفترة فحسب، بل واصل نضاله خلال مختلف مراحل الثورة الجزائرية، وكان له حضور فعّال طيلة سنوات الكفاح المسلح. ويأتي هذا العمل كمحاولة متواضعة لإبراز إسهامات هذه الشخصية التاريخية، ويبقى مفتوحًا للتطوير والإثراء من خلال دراسات مستقبلية تتيح للباحثين تعميق البحث في تاريخنا الوطني بكل أبعاده. الكلمات المفتاحية: عمار بن عودة - الثورة الجزائرية - الولاية التاريخية الثانية -شمال قسنطينة - هجومات 20 أوت 1955 - مؤتمر الصومام - مفاوضات إيفيان - الحركة الوطنية الجزائرية - النضال السياسي. Abstract : Our study falls within the scope of historical research that focuses on the history of our glorious revolution and highlights the influential figures who shaped it—particularly during the period of the immortal November Revolution. Through this work, we aim to shed light on the prominent personality of Mujahid and leader Ammar Ben Aouda – may he rest in peace – who played a crucial role prior to the outbreak of the Algerian Revolution, notably through his involvement in the Secret Military Organization, and in the decisive moments leading up to the revolution, including participating in the decision-making and preparation for its launch. His role did not stop there; he continued his revolutionary path through various stages of the Algerian Revolution, contributing actively throughout its historical phases. This work represents a modest attempt to highlight the contributions of a distinguished figure in our national history. It also serves as an open invitation for further research, paving the way for future studies that can broaden the horizons of historical exploration for researchers. Keywords :Ammar Ben Aouda - Algerian Revolution - Second Historic Wilaya - North Constantine - August 20, 1955 Attacks -Soummam Congress - Evian Negotiations - Algerian National Movement - Political Struggle.
نشاته و مشاركته في الثورة التحريرية 1925-1962م